FOMO in the Digital Age: A Study of Self-Esteem and Social Media Effects on North Sumatran Youth - Purba, Putri Annisa; Metia, Cut (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study investigates the phenomenon of Fear of Missing Out (FOMO) in North Sumatran society, particularly among Generation Z, in relation to self-esteem and social media usage. The research employs a quantitative approach with a correlational survey design, involving a sample of 150 respondents aged 12-24 years from various regions in North Sumatra who are active users of social media platforms. The study utilizes three main questionnaires: FOMO scale, social media addiction scale, and self-esteem scale. Multiple regression analysis is used to determine the involvement of each independent variable (self-esteem and social media usage) in the dependent variable (FOMO). The results reveal that both self-esteem and social media usage have a significant positive influence on FOMO. Interestingly, higher self-esteem is found to be associated with increased FOMO, suggesting that self-esteem in this context may be contingent on social validation and can strengthen the desire for digital existence. The high use of social media platforms also reinforces a sense of connectedness and a desire to socialize, which, if unfulfilled, can lead to anxiety due to the fear of being left behind. The study highlights the importance of understanding the quality of self-esteem in the current cultural and digital context and the need for digital literacy based on Islamic values to promote critical awareness of social expectations manipulated in digital spaces. The findings have practical implications for creating strategies to improve the identity and psychological resilience of young people amidst the digital culture in North Sumatra.